Mental Health - World Bank (Washington, DC, 2012)
The response on why to address mental health, lies on the fact that neuropsychiatric disorders account for an eleven percent of the global burden of disease; that four, of the top ten causes of disability were due to mental disorders; and, that depression is projected to rank second among neurological disorders. Thus, the catastrophic costs of mental disorders for individuals, and families can tip them into poverty, and it is emphasized that poor people are more likely to have symptoms of mental disease. And, while myths about the causes of mental illness abound, it is now known that these are caused by an interaction of social, genetic, traumatic, and infectious factors. As a starting point, the note indicates that an increased awareness on the causes, prevention, and interventions of mental disorders should be promoted, as should increasing numbers of health workers, and providers in such areas. It is also suggested that demand for mental, and neurological services needs to be voiced, through health education programs to combat the stigma, and raise awareness of what mental disorders really are.